1992
DOI: 10.2135/cropsci1992.0011183x003200060031x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Seedling and First‐Bloom Plant Characteristics: Relationships with Drought‐Influenced Boll Abscission and Lint Yield

Abstract: Root growth and distribution are important plant adaptations to conditions where limited soil water availability is a major constraint to crop growth and yield. Field studies were conducted to evaluate root characteristics at seedling stage and first bloom of six cotton (Gossypium hirsutum L.) genotypes, and to determine the relationship between root growth parameters and drought‐influenced boll abscission and lint yield. Genotypes included in the studies were: Tamcot SP37H (SP37H), Tamcot CD3H (CD3H), TX‐CABU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The genotypes differed significantly in total leaf area at each of these samplings. Similarly, Cook and El-Zik (1992) compared seedlings from six cotton genotypes under normal and drought stressed field conditions and found that root dry weight, shoot dry weight and root-to-shoot ratio, varied among genotypes when sampled 28 DAP. While genotypes differed significantly in both total leaf area and total leaf biomass, specific leaf area (on a total leaf area basis) was 17 DAP Genotype 25 *** *** *** *** *** *** *** nS the same for all genotypes (data not shown).…”
Section: Genotypic Variation In Early Vigor Traitsmentioning
confidence: 99%
“…The genotypes differed significantly in total leaf area at each of these samplings. Similarly, Cook and El-Zik (1992) compared seedlings from six cotton genotypes under normal and drought stressed field conditions and found that root dry weight, shoot dry weight and root-to-shoot ratio, varied among genotypes when sampled 28 DAP. While genotypes differed significantly in both total leaf area and total leaf biomass, specific leaf area (on a total leaf area basis) was 17 DAP Genotype 25 *** *** *** *** *** *** *** nS the same for all genotypes (data not shown).…”
Section: Genotypic Variation In Early Vigor Traitsmentioning
confidence: 99%
“…Exotic genotypes of cotton were reported to have larger roots and a larger root:shoot ratio than commercial cultivars (McMichael and Quisenberry, 1991). Under drought stress, lint yields of six cotton genotypes were reported to be negatively correlated to rootrshoot ratio (Cook and El-Zik, 1992). These four reports suggest that high yielding cultivars may have smaller root volumes and a decreased potential for N uptake from the soil.…”
Section: Introductionmentioning
confidence: 96%
“…These results imply that drought tolerant ramie cultivars better adapt to drought stress by maintaining their leaves and improving cuticular integrity rather than reducing the total amount of leaf exposure to the environment. Critical factors for drought tolerance are the abilities of roots to extract water from soils with limited water availability and to store this water for later use (Cook and El-Zik 1992). Previous studies have shown that higher root-to-shoot ratios help crops tolerate soil drought and maintain higher yields in moisture deficit environments (Li 1993;He et al 1995;Adam et al 2002).…”
Section: Discussionmentioning
confidence: 99%